The Others in Charlotte Brontë’s Jane Eyre: A Postcolonial-Orientalist and Feminist Reading - Filiz Barın Akman (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi, 2019)
There are different forms of othering in Charlotte Brontë’s Jane Eyre: one which results from Jane’s ambiguous position in terms of class hierarchies and another generated by Bertha’s presence as a colonized subject. In both cases, femininity amplifies gender-specific repercussions in these othering processes. However, while Brontë creates a female character in Jane who triumphs over the challenges posed by Victorian society’s class and gender hierarchies, i.e., the status as other of governesses and women, problematic as it is in its final solidification of the status quo, Bertha reflects the dominant, Eurocentric ideologies of nineteenth century England concerning race and the racial other. She is the colonized and racial other, a madwoman who threatens British men as embodied in Mr. Rochester, and women embodied as in Jane, and her final self-destruction for Jane’s sake are poignant plot devices to this end. This paper offers a comparative reading of two female characters’ othered status in Victorian British society in relation to the dominant ideologies of the era concerning gender, class and race. I argue that whereas Brontë, following a feminist reading of her novel, fictively assuages the othered status of British women in the characterization of Jane, who triumphs in resisting society’s rigid class boundaries and women’s subordinate position in terms of legal and financial matters, does not grant a similarly fictive emancipatory view to Bertha as the colonized and racial other. This is an obvious and clear indication of Brontë’s limitations concerning feminist activism and inclusiveness as her implication in advancing the dominant, imperialist discourse.